Reindeer 24-hr within and between group synchronicity in summer versus environmental variables - Colman, Jonathan E.; Eidesen, Ruben; Hjermann, Dag; Gaup, Mathis A.; Holand, Øystein; Moe, Stein R.; Reimers, Eigil (Rangifer, 2004)
Abstract: The impact of abiotic stimuli on the circadian activity rhythm of Rangifer has long been debated. Their highly gregarious and mobile behaviour presupposes synchronized behaviour within a group, while a predominant abiotic influence would be expected to synchronize separate, independent groups subjected to the same environment. We tested within and between group synchronization of semi-domestic reindeer during summer observing 6 independent groups located in close proximity to each other. We also tested how some external environmental factors affected the animals’ behaviour. Activity of all individuals (3 females in 6 groups, n = 18 reindeer) was recorded every 10 minutes 24-hrs a day, along with weather variables and biotic factors such as insect harassment. Data were divided into two periods of 8 and 6 days, respectively, separated by a period of 6 days. Animals within a group showed highly synchronized behaviour, reflected in overlapping periods of grazing and ruminating. There was little or no synchronization between groups, reflected by little or infrequent overlapping of activities amongst some of the groups. Rarely were all 6 groups active or inactive simultaneously. There was no consistent or significant influence on the reindeers’ behaviour by any of the environmental variables recorded. Thus, and as expected, in the absence of external environmental stimuli, the activity of individuals within a group was synchronized. However, there was no synchronization amongst independent groups. This supports the claim that during summer, in the absence of disturbance from stimuli such as insect harassment or anthropogenic activities, reindeer have a 24-hr polycyclic activity rhythm independent of climatic variables. Instead of abiotic factors, such as light, reindeers’ activity rhythms were defined by internal physiological processes and intra-specific group interactions reflected in almost complete within group synchronization and lack of between group synchronization. Abstract in Norwegian / Sammendrag: Betydningen av abiotiske variabler på reinens døgnrytme har lenge vært diskutert. Med sin gruppeadferd og mobilitet forventer man samhandling innenfor ei gruppe, mens abiotiske variabler faktorer forventes å synkronisere adferden mellom adskilte grupper i samme miljø. Vi testet adferdssynkroniseringen innenfor og mellom grupper av tamrein ved å observere aktiviteteter i seks uavhengige grupper hver med tre simler. Vi testet også hvordan noen miljøvariabler påvirker dyrenes adferd. Aktiviteten til alle individene ble observert hvert tiende minutt hele døgnet sammen med klimatiske forhold og biotiske variabler som insektplage. Dyrene innenfor ei gruppe viste klart felles adferd med samme beite- og liggeperioder. Det var lite eller ingen synkronisering mellom grupper, idet det var lite eller tilfeldig sammenfall av aktiviteter. Sjelden var alle seks gruppene aktive eller inaktive samtidig. Aktiviteten til individer innenfor en gruppe var synkronisert som forventet, uten eksterne miljøvariabler. Derimot var det ingen synkronisering mellom uavhengige grupper. Dette støtter teorien at reinsdyr har en 24-t polysyklisk aktivitetsrytme uavhengig av klimatiske variabler på sommeren og uten sterke påvirkninger utenfra som parasittiske insekter eller menneskelige aktiviteter. Vårt forsøk viste at reinens aktivitetsrytme tydeligvis var definert av interne fysiologiske prosesser og interaksjoner innen gruppen.